Pengaruh Physical Attractiveness dan Source Credibility Celebrity Endorsement pada Produk Somethinc terhadap Word of Mouse melalui Customer Attitude - Adinda El Maura; Wira Bharata (Universitas Batanghari, 2023)
Using celebrities to support brands and business e-commerce is a new strategy in Indonesia. Therefore, it is very important to know the factors that influence consumer attitudes. This study aims to explore the relationship between celebrity physical attractiveness, celebrity credibility, and word of mouse. This research was conducted on social media users who use and buy somethinc products. The sample of this research is social media users who use and buy somethinc products because of Tasya Farasya. The total sample for this survey is 107 respondents. The analysis technique used is the equationstruktural Partial Least Squares Modeling (SEM-PLS). The results of this study indicate that the Physical Attractiveness and Source Credibility Celebrity Endorsement on Somethinc Products has a positive effect on Word of Mouse through Customer Attitude.